Undefined xylose media extracted from biorefinery waste for enhanced and eco-friendly production of cephalosporin C by Acremonium chrysogenum M35 - Kim, Sungbong; Kim, Hyeong Ryeol; Oh, Hyun Ju; Lee, Kyu-Tae; Um, Youngsoon; Kim, Dong Wook; Seo, Sang Woo; Park, Chulhwan; Kim, Seung Wook (Wiley-VCH Verlag, 2023)
Xylose-rich undefined broth, extracted from the dilute acid pretreatment wastes of barley straw, serves as resourceful media for Acremonium chrysogenum M35 culture and production of cephalosporin C (CPC). Concentrating the extract with proper reprocessing enables to prepare various concentrations of xylose broth (2%-8%). The undefined xylose media were prepared for CPC production from A. chrysogenum M35 by the addition of other nutrients. Cell growth and CPC production were the most effective at 6% xylose and additional 2% glycerol, with maximum CPC production of 9.07 g/L after 6 days, which is higher production than that in defined media prepared with laboratory-level nutrients and reagents. Investigation of autotrophic and reverse trans-sulfuration pathways for cysteine synthesis, a limited element of three precursors for CPC synthesis, supports the enhanced CPC production in undefined media. Abundance of xylose ensures a maintained NADPH concentration required for sulfate reduction and synthesis of amino sulfide such as cysteine. Cystathionine-gamma-lyase activity profiling indicated more efficient biosynthesis in undefined media than in other cultures use glycerol and glucose, and the biosynthesis pathway of CPC production by the cephalosporin gene cluster (i.e. pcbC and cefG genes) was investigated. The process using undefined xylose media was designed, and process simulation program confirmed our results.